2016
DOI: 10.1182/bloodadvances.2016000927
|View full text |Cite
|
Sign up to set email alerts
|

Therapy and outcomes of primary central nervous system lymphoma in the United States: analysis of the National Cancer Database

Abstract: Although the role of radiation therapy and chemotherapy in primary central nervous system lymphoma (PCNSL) has evolved considerably over the past decade, the application of treatment modalities in the community has not been evaluated. We analyzed the use of chemotherapy, radiation therapy, and associated overall survival, among 9165 HIV-negative PCSNL cases reported to the US National Cancer Database in 2004-2013. During this time, the proportion of patients receiving chemotherapy significantly increased from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 40 publications
5
24
1
Order By: Relevance
“…23,[26][27][28] Hence, patients aged over 60 years represented 72% of the study population, including 43% of patients aged over 70 years. This age distribution has also been reported in another recent cohort 29 and is in line with epidemiologic studies reporting a continuously increasing rate in the elderly over last decades. 30,31 This trend remains unelucidated and is likely to continue in the near future with population aging and the increasing need for brain biopsy in the elderly.…”
Section: Discussionsupporting
confidence: 91%
“…23,[26][27][28] Hence, patients aged over 60 years represented 72% of the study population, including 43% of patients aged over 70 years. This age distribution has also been reported in another recent cohort 29 and is in line with epidemiologic studies reporting a continuously increasing rate in the elderly over last decades. 30,31 This trend remains unelucidated and is likely to continue in the near future with population aging and the increasing need for brain biopsy in the elderly.…”
Section: Discussionsupporting
confidence: 91%
“…Although PNCSL represents a rather rare CNS malignancy, a number of controlled trials have investigated promising cyto-reductive treatment regimens [6] . During recent years, whole brain radiation has been applied less frequently, since it bears almost no curative potential, although initial response to therapy is striking [7] . Multidrug-chemotherapy approaches, mostly based on methotrexate, are increasingly performed with beneficial outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This probably reflects the effect of salvage therapy (such as WBRT) that prolongs survival beyond progression regardless of its negative impact on quality of life. Notably, outcomes of published treatment series do not reflect the “real-life” experience where median OS of the elderly remained in the range of 6–7 months [1, 19]. However, HD-MTX is relatively safe treatment for PCNSL patients regardless of age [23], and even patients aged 80 years or more can tolerate the HD-MTX regimen (such as MPV) [12].…”
Section: Diagnosis and Treatment Of Elderly Patients With Pcnslmentioning
confidence: 99%
“…Nevertheless, several studies have shown that fit patients above the age of 60 years can tolerate high-dose chemotherapy and even an intensive up-front treatment with a high overall response rate reported (range: 60–89%) including a proportion of long-term survivors (Table 1) [3-17]. Yet, many clinical trials exclude patients above the age of 70 years [11, 18], and about a quarter of PCNSL patients older than 70 years who survive more than 3 months from diagnosis do not receive chemotherapy at all [19]. The fraction of patients who have not been treated with chemotherapy increased from 14 to 23, and to 44% in the age groups of 61–70, 71–80, and > 80 years, respectively.…”
Section: How To Define “Elderly” Pcnsl Patientsmentioning
confidence: 99%